Role of non-high-density lipoprotein cholesterol as a risk factor in ischemic stroke - Dangudubiyyam S S R K Pavan; Prabhu Gnanasekaran (The Bioscan, 2025)
Introduction: The present study highlights the significance of non-high-density lipoprotein cholesterol (non-HDL-C) as a key risk factor for ischemic stroke. A thorough analysis revealed a strong correlation between elevated non-HDL-C levels and an increased risk of ischemic stroke. These findings underscore the importance of incorporating non-HDL-C testing into routine clinical practice to enhance risk assessment and preventive strategies. By identifying individuals at heightened risk based on non-HDL-C levels, healthcare providers can implement targeted interventions—such as lifestyle modifications and pharmacological treatments—to effectively reduce the likelihood of ischemic stroke. Objectives: • To measure non-HDL cholesterol levels in ischemic stroke patients. • To evaluate non-HDL cholesterol and to establish non-HDL cholesterol as an independent risk factor for ischemic stroke. Materials and methods: Fasting venous sample of 5ml was drawn and lipid profile levels like Total Cholesterol (TC), Triglycerides (TGL), Low Density Lipoprotein Cholesterol (LDL-C) and High-Density Lipoprotein Cholesterol (HDL-C) were performed. Non-HDL-C was calculated. Results: All the patients in the study had experienced CVA-Infarct. A majority (70.1%) showed elevated levels of non-HDL cholesterol. Among patients with normal LDL cholesterol levels, 85.5% also had normal non-HDL levels, while 14.5% still had elevated non-HDL cholesterol. Notably, all patients with high LDL levels (100%) had elevated non-HDL cholesterol as well. The study found significant gender-based differences in mean total cholesterol, LDL, HDL, and VLDL levels. However, there was no significant difference in mean non-HDL cholesterol levels when comparing patients across different age groups. This suggests that non-HDL cholesterol levels remain consistent among stroke patients regardless of age. Conclusion: The present study emphasizes how important non-high density lipoprotein cholesterol (non-HDL-C) as a risk factor for Ischemic Stroke. The results further highlight the need for more investigation into the underlying mechanisms that connect non-HDL-C and ischemic stroke, as well as the effectiveness of particular non-HDL-C targeted therapies in lowering the incidence of stroke and enhancing outcomes.